Representação do feminino em Simão Dias - Rosa, Renata Santos (2015)
The present work focuses on the sergipan literature, more specifically the literature of Alina Paim in his work Simão Dias, we seek to observe the relationship between literature and feminism. Alina Paim is a Sergipan writer who is unfortunately little known in the literary milieu. The work has autobiographical character and our goal is to analyze the female characters and the way they are treated and react to the patriarchal society of the twentieth century. Among the various female characters is the highlight for Luisa and Do Carmo, the two women who dare to live differently from the one imposed by androcentrism. We will work on important issues such as patriarchalism, how was the education of women in Brazil, their role in marriage, all issues that are the basis for understanding the position of women in twentieth century society. Therefore, we intend to reflect on the historical role of women in society, in addition to seeking to revive the literature of Alina Paim, a brilliant but little known sergipana writer. This analysis was based on the reflections of theorists such as Simone de Beauvoir (2009), Saffioti (2004), Pateman (2008), Mary del Priore (2013), among other authors, as well as dissertation theses.